Une épistémologie numérique des disciplines est-elle possible ? Étude d’un corpus de revues francophones en sciences humaines et sociales - Max Beligné; Isabelle Lefort; Sabine Loudcher (Humanités Numériques)
The most important French-language human and social sciences journals have been digitised and published online. Digital Humanities tools make it possible in theory to obtain this important dataset and propose new epistemological readings of the disciplines. The potential of this research field is detailed, firstly in order to better understand the methods and multiple interests of a general digital epistemology and secondly to more specifically explore a digital epistemology applied to journals. Despite this considerable potential, a state of the art about digital epistemology based on French-language journals shows that there are only few research works. In order to understand this fact, three issues must be addressed: the choice of a representative corpus, the data acquisition and the data cleaning, and finally the selection of the method. Beyond the objective of a new epistemological reading of a discipline, the underlying political dimensions of this project can be highlighted.